Parasitism of terrestrial gastropods by medically-important nematodes in Brazil - Thiengo, Silvana C.; Ramos-de-Souza, Jucicleide; Silva, Guilherme M.; Fernandez, Monica A.; Silva, Elizangela F.; Sousa, Arielly K. P.; Rodrigues, Paulo S.; Mattos, Aline C.; Costa, Ruam A. F.; Gomes, Suzete R. (Frontiers in Veterinary Science, 2022)
An ample variety of parasitic associations are found between mollusks and nematodes, in which the mollusks may act as intermediate, paratenic or definitive hosts. Some free-living nematodes, in particular those of the order Rhabditida, are also found frequently in terrestrial mollusks. The present study reviews the results of the parasitological testing on samples of terrestrial mollusks conducted at the Brazilian National Reference Laboratory for Schistosomiasis and Malacology between 2008 and 2021. The samples were supplied primarily by the public health authorities from the different regions of Brazil, but also by research institutions and general population. The mollusks were processed individually and the obtained larvae were identified from their morphology and, whenever necessary, by molecular analysis. A total of 1,919 service orders were registered during the period, including 19,758 mollusk specimens collected from 23 of the 26 Brazilian states, as well as the Federal District, totalizing 145 municipalities. There was a marked predominance of the synanthropic species that are widely distributed in Brazil – Achatina fulica (87.08%), Bulimulus tenuissimus (4,18%), Bradybaena similaris (2.06%), and Sarasinula linguaeformis (1.50%). Of the 16,750 terrestrial mollusks examined, nematodes were recorded in 1,308 service orders, with the predominance of the superfamily Metastrongyloidea, in 616 service orders. They included Angiostrongylus cantonensis, rat lungworm, which was found in 252 samples, and Aelurostrongylus abstrusus in 145 samples. Free-living nematodes were found in 952 samples, Ancylostoma caninum and Cruzia tentaculata (previously identified as Strongyluris sp.) in one and 275 samples, respectively, and other parasites in 210 samples (not identified). The results highlight the diversity of the associations between nematodes and terrestrial mollusks in Brazil, in particular invasive and synanthropic species, with emphasis on the giant African land snail, Achatina fulica. They demonstrate the prominent role of this species of mollusk in the transmission of medically-important nematodes, which affect the health of both humans and animals, in particular eosinophilic meningitis, which is caused by Angiostrongylus cantonensis. This reinforces the need for more studies, and justify the growing demand for information as well as parasitological diagnosis of this mollusk, given its wide distribution in Brazil and its impact as an urban pest.